1995
DOI: 10.1016/0301-2115(95)02128-t
|View full text |Cite
|
Sign up to set email alerts
|

Single dose ceftriaxone versus single dose cefuroxime plus metronidazole for preventing febrile morbidity and urinary tract infection in vaginal hysterectomy

Abstract: Objective: To compare the prophylactic efficacy o f 1 g ceftriaxone with 1,5 g cefuroxime + 0.5 g metronidazole for febrile morbid ity and urinary tract infection in patients undergoing vaginal hysterectomy. Study design: A prospective, randomized, comparative, non-blinded study with at least 100 patients on each side. The two-sample /-test was used for testing equality o f two means and the x 2 test was used for pair differences. Results: Single dose cefuroxime + metronidazole and ceftriaxone were equally eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 4 publications
(6 reference statements)
0
6
0
Order By: Relevance
“…Also, Van der Linden et al found no difference in UTI rates in patients undergoing vaginal hysterectomy with or without colporrhaphy and receiving amoxicillin/clavulanate versus cefuroxime plus metronidazole [14]. Brouwer and Hoogkamp-Korstanje did not find a statistically significant difference regarding development of UTI in patients receiving single-dose ceftriaxone or cefuroxime plus metronidazole prophylaxis [15]. In 2004, Rogers et al, in a total of 435 patients of which 59% underwent a retropubic urethropexy and in whom suprapubic catheterization was used, found that a preoperative dose of cephalosporin plus postoperative nitrofurantoin monohydrate was associated with less development of UTI than the use of preoperative cephalosporin and placebo (7.2% vs 19.8%) [16].…”
Section: Comparisons Between Two Antibiotic Regimensmentioning
confidence: 99%
“…Also, Van der Linden et al found no difference in UTI rates in patients undergoing vaginal hysterectomy with or without colporrhaphy and receiving amoxicillin/clavulanate versus cefuroxime plus metronidazole [14]. Brouwer and Hoogkamp-Korstanje did not find a statistically significant difference regarding development of UTI in patients receiving single-dose ceftriaxone or cefuroxime plus metronidazole prophylaxis [15]. In 2004, Rogers et al, in a total of 435 patients of which 59% underwent a retropubic urethropexy and in whom suprapubic catheterization was used, found that a preoperative dose of cephalosporin plus postoperative nitrofurantoin monohydrate was associated with less development of UTI than the use of preoperative cephalosporin and placebo (7.2% vs 19.8%) [16].…”
Section: Comparisons Between Two Antibiotic Regimensmentioning
confidence: 99%
“…1. After triage, there were 90 remaining studies that were included in the meta‐analysis [6–9, 12–96]. Of these 44 were sourced from Medline, an additional 8 from Embase, 10 from the Cochrane registers, 10 from scientific meetings, and 18 from identified references.…”
Section: Resultsmentioning
confidence: 99%
“…The difference in antibiotic performance was significant after general abdominal–gastrointestinal operations (including studies that looked at a range of abdominal surgery, and colorectal surgery but not for upper gastrointestinal or biliary surgery [6–9, 13, 15, 20, 23, 24, 30, 36, 43, 46, 51, 55, 57, 62, 77] and pelvic surgery. The differences were most significant after colorectal surgery ( n = 6; OR 0.3; 95% CI 0.16–0.58; p < 0.001) and obstetric and gynecological (O&G) surgery ( n = 9; OR 0.53; 95% CI 0.34–0.69) [17, 39, 47, 63, 68, 71, 73, 75, 79]. There was no difference in antibiotic performance for clean operations, which included mainly cardiac surgery and orthopedic operations [27, 37, 48, 65, 69].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ceftriaxone is a longacting, third-generation cephalosporin which has shown good results in the treatment and prophylaxis of infections in various parts of the body [10]. It has shown in vitro and in vivo activity against known pathogens that cause infection following vaginal hysterectomy [13], against colorectal organisms and against organisms that cause urinary infection [14]. Because of its relative high cost in our economically impoverished community we were unable to give more than the first dose.…”
Section: Discussionmentioning
confidence: 99%